AGAMA DAN MEDIA: PENGAWASAN AGAMA TERHADAP PERKEMBANGAN TIK - Husnul Qodim (Khazanah Multidisiplin, 2023)
Information and Communication Technology (ICT) has developed very rapidly, one of the negative impacts that has arisen is the emergence of the phenomenon of blasphemy, mutual attacks, and even hostility to each other. Thus, the media now seems to be an inseparable part of everyday life. Many previous studies have discussed ICT, but this research tries to reveal contemporary issues regarding ICT and how religion functions in technological development. Using the library research method, it was found that there were at least 6 of them, namely selfies, cyberwar, online shopping, personalization of users, and a culture of sharing and to guard it using the concept of social piety.